Tourism Research and Landscape Interpretation - Tourismusforschung und Landschaftsinterpretationen - Kreisel, Werner (Universitätsverlag Göttingen, 2019)
The central task of tourism research is to advocate for sustainability. In order to do justice to the various components relating to tourism, such as aspects of the natural and cultural landscape as well as the economic, sociocultural and political situation, an integrative approach is necessary. The "landscape" is the foundation of tourism. Landscapes have their own value, a value that visitors and even locals are often not conscious of. "Landscape interpretation" and "heritage interpretation" attempt to remedy this defi cit by defi ning, vividly presenting and "staging" the essential aspects of a landscape. This makes it possible to enhance awareness of the value of a landscape and its need to be protected, thereby achieving a positive change in the behaviour of visitors. The present volume introduces various initiatives, which illustrate the importance of landscape interpretation for tourism research.